Biodegradation of unpretreated low-density polyethylene (LDPE) by thermophiles isolated from Paku hot springs water and sediment in Sarawak, Borneo, Malaysia - Sabrina Rancang Khairul,; Seng, Chiew Toh; Arlene Debbie Lingoh,; Sui, Sien Leong (Penerbit Universiti Kebangsaan Malaysia, 2025)
Plastic pollution has emerged as a significant environmental concern nowadays, necessitating innovative solutions for its mitigation. Hot springs, while traditionally valued for their health and relaxation benefits, also present unique environments that may harbour thermophile bacteria species capable of degrading plastic polymers. The study aimed to screen thermophiles from Sarawak hot springs for the biodegradation of potential low-density polyethylene (LDPE) film and evaluate their efficiency in degrading the plastic in 30 days. Water and sediment samples were collected from each pond of the Paku hot spring in Sarawak, Borneo, Malaysia, in triplicate. The thermophiles were cultivated in an enriched medium supplemented with 0.5% (w/v) PE powder at 55°C for 5 days. Colony morphology and Gram staining were carried out. Screening of isolates for LDPE biodegradation was conducted using the BATH test and, clear zone assay. Additionally, the efficiency of the isolates for 30 days of LDPE biodegradation was evaluated using the pH change, bacteria growth observation, and weight loss method. A total of 96 thermophilic isolates were cultured, 11 isolates exhibited hydrophobicity levels above 30%, and 7 isolates showed clear zone formation. After the biodegradation process, the pH was slightly decreased to pH 6.5. The bacterial colonies were Gram-positive (3) and Gram-negative (4) short rods. Isolates SPK(W)M1(1), SPK(SD)P1(2), and SPK(SD)P1(3) resulted in increased of growth (OD600 0.06 ± 0.02, OD600 0.08 ± 0.01 & OD600 0.1 ± 0.02, respectively). The highest growth absorbance OD600 was shown by isolate SPK(SD)P1(3), while isolate SPK(W)M1(1) showed the highest LDPE film weight reduction of 10 % (0.45 ± 0.05 g). The thermophiles SPK(SD)P1(3) and SPK(W)M1(1) are potentially to be used to biodegrade LDPE plastic. The preliminary study offers insight into microbial biodegradation mechanisms; further research and advanced sequencing techniques are necessary for a thorough analysis of the metabolic pathways involved.